2019
DOI: 10.1101/610006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Gly/NMDAR Antagonist from Chromolaena odorata’s Derived Phytoconstituents using Induced Fit Docking Approach

Abstract: The ionotropic activation of N-methyl-D-aspartic acid (NMDA) plays a significant role in different type of neurodegenerative disease, as it is a tetramer with two Glycine binding subunit and two glutamate subunits. NMDA receptor can be inhibited by either blocking of the glycine site or glutamate site. Previously reported inhibitors of NMDA receptor focus on the inhibition of the glutamate subunit, which was reported to be associated with side effects such as ataxia, memory deficits, neurotoxicity. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ugale and Bari reported that amino acid residues Arg131, Pro124, and Thr126 are essential for inhibiting the Gly/NMDA receptor [70,71]. These interactions were also noticed by Devid et al [72] with some additional interactions (GLN13, ASP224, and Trp223 residues). Our results are in correspondence with these previous reports.…”
Section: Nmda-complexmentioning
confidence: 52%
“…Ugale and Bari reported that amino acid residues Arg131, Pro124, and Thr126 are essential for inhibiting the Gly/NMDA receptor [70,71]. These interactions were also noticed by Devid et al [72] with some additional interactions (GLN13, ASP224, and Trp223 residues). Our results are in correspondence with these previous reports.…”
Section: Nmda-complexmentioning
confidence: 52%
“…Moreover, many studies have previously reported that certain phytochemicals have neuroprotective properties such as protocatechuic acid [90,91], syringic acid [91,92], vanillic acid [93], gallic acid [91], 4-hydroxybenzoic acid [94], chlorogenic acid [91], luteolin [95], quercetin [95], taxifolin [96], quercetin-3-O-rutinoside (rutin) [95], and isoorientin [97]. Furthermore, in silico studies have predicted that certain plant phytochemicals have NMDAR antagonist activity and could prevent L-Glu excitotoxicity, such as chlorogenic acid [98], quercetin, gallic acid, protocatechuic acid, and vanillic acid [99], and the LC-MS results from this study confirm that acai berry extracts contain these phytochemicals (Table 1). This implies that acai berry extracts may retain a range of phytochemicals that have antioxidant and anti-excitotoxicity effects that could be neuroprotective and reduce vulnerability to excessive L-Glu levels such as those associated with NDDs and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid residues PRO124, THR126, and ARG131 are crucial for blocking the Gly/NMDA receptor, according to Ugale and Bari [25,70]. With some additional interactions (GLN13, TRP223, and ASP224), Devid et al [71] also noted these interactions. Our findings are consistent with these earlier publications.…”
Section: Molecular Interaction Analysis Of N-methyl-d-aspartate Recep...mentioning
confidence: 99%